Tobramycin Inhalation Powder (TIP): An Efficient Treatment Strategy for the Management of Chronic Pseudomonas Aeruginosa Infection in Cystic Fibrosis - Lam, John (Libertas Academica, 2013)
Repeated bouts of acute and chronic lung infections are responsible for progressive pulmonary function decline in individuals with cystic fibrosis (CF), ultimately leading to respiratory failure and death. Pseudomonas aeruginosa is the archetypical CF pathogen, causes chronic infection in 70% of individuals, and is associated with an accelerated clinical decline. The management of P. aeruginosa in CF has been revolutionized with the development and widespread use of inhaled antibiotics. Aerosol delivery of antimicrobial compounds in CF enables extremely high concentrations of antibiotics to be reached directly at the site of infection potentially overcoming adaptive resistance and avoiding the potential for cumulative systemic toxicities. Tobramycin inhalation powder (TIP) represents the first dry powder inhaled (DPI) antibiotic available for use in CF. DPIs are notable for a markedly reduced time for administration, ease of portability, and increased compliance. TIP has been developed as a therapeutic alternative to tobramycin inhalation solution (TIS), the standard of care for the past 20 years within CF. Relative to TIS 300 mg nebulized twice daily in on-and-off cycles of 28 days duration, TIP 112 mg twice daily via the T-326 inhaler administered on the same schedule is associated with marked time savings, increased patient satisfaction, and comparable clinical end points. TIP represents an innovative treatment strategy for those individuals with CF and holds the promise of increased patient compliance and thus the potential for improved clinical outcomes.